Flavones inhibit breast cancer proliferation through the Akt/FOXO3a signaling pathway. Issue 1 (December 2015) - Lin, Chia-Hung; Chang, Ching-Yao; Lee, Kuan-Rong; Lin, Hui-Ju; Chen, Ter-Hsin; Wan, Lei
Abstract Background Flavones found in plants display various biological activities, including anti-allergic, anti-viral, anti-inflammatory, anti-oxidation, and anti-tumor effects. In this study, we investigated the anti-tumor effects of flavone, apigenin and luteolin on human breast cancer cells. Methods The anti-cancer activity of flavone, apigenin and luteolin was investigated using the MTS assay. Apoptosis was analyzed by Hoechst 33342 staining, flow cytometry and western blot. Cell migration was determined using the culture inserts and xCELLigence real-time cell analyzer instrument equipped with a CIM-plate 16. Real-time quantitative PCR and western blot were used to determine the signaling pathway elicited by flavone, apigenin and luteolin. Results Flavone, apigenin and luteolin showed potent inhibitory effects on the proliferation of Hs578T, MDA-MB-231 and MCF-7 breast cancer cells in a concentration and time-dependent manner. The ability of flavone, apigenin and luteolin to inhibit the growth of breast cancer cells through apoptosis was confirmed by Hoechst33342 staining and the induction of sub-G1 phase of the cell cycle. Flavone, apigenin and luteolin induced forkhead box O3 (FOXO3a) expression by inhibiting Phosphoinositide 3-kinase (PI3K) and protein kinase B (PKB)/Akt. This subsequently elevated the expression of FOXO3a target genes, including the Cyclin-dependent kinase inhibitors p21Cip1 (p21) and p27kip1 (p27), which increased the levels of activated poly(ADP) polymerase (PARP) and cytochromec . Conclusion Taken together, these data demonstrated that flavone, apigenin and luteolin induced cell cycle arrest and apoptosis in breast cancer cells through inhibiting PI3K/Akt activation and increasing FOXO3a activation, which suggest that flavone, apigenin and luteolin will be the potential leads for the preventing and treating of breast cancer.